Dab1 Binds to Fe65 and Diminishes the Effect of Fe65 or LRP1 on APP Processing - Kwon, Oh Yeun; Hwang, Kyounghee; Kim, Jeom-A; Kim, Kwangmyung; Kwon, Ick Chan; Song, Hyun Kyu; Jeon, Hyesung (WILEY, 2010)
Fe65 and Dab1 are adaptor proteins that interact with the cytoplasmic domain of amyloid precursor protein (APP) via phosphotyrosine-binding (PTB) domain and that affect APP processing and A beta production. Co-expression of Dab1 with Fe65 and APP resumed nuclear translocation of Fe65 despite of its cytoplasmic anchor, APP. The decreased amount of Fe65 bound to APP was shown in co-immunoprecipitation assay from the cells with Dab1 which also displayed the effect on APP processing. These data suggested that Fe65 and Dab1 compete for binding to APP. Surprisingly, we found that Fe65 interacts with Dab1 via C-terminal region of Dab1 and unphosphorylated Dab1 is capable of binding Fe65. Dab1 interacts with the low-density lipoprotein receptor-related protein (LRP) as well as APP through its PTB domain. Dab1 significantly decreased the amount of APP bound to LRP and the level of secreted APP and APP-CTF in LRP expressing cells, unlike Fe65. It implies that overexpression of Dab1 diminish LRP-APP complex formation, resulting in altered APP processing. The competition for overlapped binding site among adaptor proteins may be related to the regulation mechanism of APP metabolism in various conditions. J. Cell. Biochem. 111: 508-519, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: AMYLOID PRECURSOR PROTEIN; RECEPTOR-RELATED PROTEIN; ALZHEIMERS-DISEASE; ADAPTER PROTEIN; BRAIN-DEVELOPMENT; APOE RECEPTOR; DISABLED 1; INTRACELLULAR DOMAIN; CYTOPLASMIC DOMAIN; CYTOSOLIC ADAPTER